National geographic distribution and number of TV nature programs across the Japanese archipelago - Tachibana, Kousuke; Uchida, Kei; Aiba, Masahiro; Sasaki, Takehiro (Ecological indicators, 2021)
•The studied programs broadly dealt with nature, including travel and education ones.•The number of nature programs in Japan was greater in mountainous than coastal areas.•The number of nature programs was associated with the presence of famous mountains.•Temporal changes in spatial distribution of nature programs reflected social trends. Cultural ecosystem services (CES) represent the intangible dimensions of the links between people and ecosystems. The evaluation and mapping of CES are critical and can be deeply involved in policy and decision-making concerning the management of ecosystems. Many previous studies have evaluated CES occurred through on-site and proximate contacts with nature such as walking in the forest, watching wildlife, or enjoying landscapes. However, fewer studies evaluated CES occurred in an off-site and distant way through conventional media such as TV and radio, and their spatially explicit evaluations are particularly rare. This paper focused on nature TV programs in Japan as an indicator of CES related to education, aesthetic enjoyment, and nature experience. We revealed the geographical distribution of nature programs across the Japanese archipelago. The associations of the number of TV programs with a range of key factors are discussed. The number of nature programs, and the temporal trends in such associations are explained. We obtained 4,117 nature programs that covered 1,691 locations across the Japanese archipelago between 2004 and 2017. We found that many nature programs dealt with World Natural Heritage Sites (WNHS) and World Cultural Heritage Sites (WCHS), including the Shiretoko peninsula (85 programs), Yakushima island (35 programs), Mt. Fuji (52 programs), and the mountainous areas around the Japanese Alps. In general, the number of Hyakumeizan (100 famous Japanese mountains) and the proportion of WNHS, WCHS, and lake areas within the search radii of 5, 10, and 15 km from the geotagged location of nature program were significantly positively correlated with the number of nature programs across the study period (2004–2017). In particular, the presence of famous mountains has become a relevant predictor of the number of nature programs since around 2012, consistent with the rise of mountaineering and hiking trends in Japan. Our result suggests that the designation as WNHS and WCHS would facilitate maintaining and managing invaluable nature and cultural landscapes of outstanding universal value, and thereby contributing to provide CES through TV programs.